Universities as stakeholders in their students' careers: On the benefits of graduate taxes to finance higher education - Tom McKenzie; Dirk Sliwka (Institute for the Study of Labor (IZA), 2010)
We examine ways of funding higher education, comparing upfront tuition fees with graduate taxes. The tax dominates, as volatility in future income is transferred from risk-averse students to the risk-neutral state. However, a double moral hazard problem arises when students' efforts to raise lifetime income and universities' activities to improve teaching quality are endogenized. We show that graduate taxes reduce work incentives but provide incentives to improve teaching quality. Yet if tax revenues are distributed evenly among universities there is free riding. To solve this problem each university should be allocated the revenue generated by its own alumni. In addition, we demonstrate how a budget-balancing graduate tax would encourage more people to attend university than would the equivalent upfront tuition fee.
Keywords: H42; H52; I22; M52; 330; higher education; graduate tax; tuition fees; risk aversion; incentives